2015
DOI: 10.1007/s11196-015-9440-y
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Achievement in the International Criminal Tribunal for the Former Yugoslavia (ICTY): A Corpus-Based Critical Discourse Analysis

Abstract: The International Criminal Tribunal for Yugoslavia (ICTY) was established by the UN Security Council in 1993 to prosecute persons responsible for war crimes committed in the former Yugoslavia during the Balkan wars. As the first international war crimes tribunal since the Nuremburg and Tokyo tribunals set up after WWII, the ICTY has attracted immense interest among legal scholars since its inception, but has failed to garner the same level of attention from researchers in other disciplines, notably linguistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Previous studies have found broad correlation between specific events (such as the September 11 terrorist attacks) and overall rates of asylum acceptance (Neumayer 2005;Rottman et al 2009). More computationally driven approaches have used sentiment analysis to examine the role of a discourse of 'achievement' in the case law of a court (Potts and Kjaer 2016). NLP has similarly been used to examine how courts grapple with politically sensitive issues (Busch and Pelc 2019).…”
Section: Countrymentioning
confidence: 99%
“…Previous studies have found broad correlation between specific events (such as the September 11 terrorist attacks) and overall rates of asylum acceptance (Neumayer 2005;Rottman et al 2009). More computationally driven approaches have used sentiment analysis to examine the role of a discourse of 'achievement' in the case law of a court (Potts and Kjaer 2016). NLP has similarly been used to examine how courts grapple with politically sensitive issues (Busch and Pelc 2019).…”
Section: Countrymentioning
confidence: 99%
“…The corpus-assisted approach marks an emerging characteristic of current Corpus Linguistics, which is that it supports and is supported by other approaches to language. For example, Potts and Kjaer [87] combine Corpus Linguistics methods with Critical Discourse Analysis [30] to explore how 'achievements' are discursively constructed in the texts created by the International Criminal Tribunal for Yugoslavia. The combination includes quantitative corpus linguistic methods, which help to quantify, visualize and detect patterns of meaning in data, and a qualitative theory of Critical Discourse Analysis useful for shaping and informing the explorations of the quantitative results.…”
Section: What Is Corpus Linguistics Today?mentioning
confidence: 99%
“…[22]) or analysis of the 'voice' of Tribunals (e.g. [41]). Therefore, this article illustrates some of the latest work being undertaken at the legal-linguistic interface.…”
Section: Theoretical Overview Of Linguistic Perspectives and Previousmentioning
confidence: 99%